Teanol, a new brominated sesquiterpene from the Thailand Laurencia mariannensis - Yu Minamida; Hiroshi Matsuura; Charles Santhanaraju Vairappan; Sutti Suttikarn; Tsuyoshi Abe; Minoru Suzuki (2020)
We examined the constitution of Laurencia mariannensis collected from the east coast of Tean Island, Thailand. The structure of a new brominated rearranged cyclolaurane-type sesquiterpene, named teanol (1), is reported. This is the first report on biology and chemistry of the Thailand red algal genus Laurencia (Rhodomelaceae, Ceramiales).